Effect of Lockdown due to COVID-19 on the Aerosol and Trace Gases Spatial Distribution over India and Adjoining Regions - Madineni Venkat Ratnam; Perumal Prasad; Sivan Thankamani Akhil Raj; Ibrahim Hoteit (Aerosol and Air Quality Research)
Abstract Significant improvement in the air quality has been reported during the ‘Lockdown’ being implemented due to the Corona Virus Disease (COVID-19) pandemic in several parts of the globe. Using Ozone Monitoring Instrument (OMI) satellite measurements, we found a 50–60% reduction in the mean tropospheric columnar Nitrogen dioxide (NO2) and planetary boundary layer Sulphur dioxide (SO2) levels over India and adjoining regions during the lockdown (25 March–7 April 2020) compared to the pre-lockdown periods (8–21 March 2020). Similar decreases in aerosol concentrations over Indo-Gangetic Plain (IGP) and south India during lockdown are noticed in Moderate Resolution Imaging Spectroradiometer (MODIS) measurements, reaching the lowest values in the satellite era. Surprisingly, aerosol concentrations increased significantly (50–70%) during lockdown over central India when compared to pre-lockdown and climatology (2001–2019). A Concentration Weighted Trajectory analysis suggests that the air masses traveling from middle-east and Africa are the potential sources for the observed high aerosol concentrations over central India. Changes in the background meteorology (decrease in wind speed and increase in water vapour) during the lockdown made these aerosols stagnant and increased their size over central India, leading to higher AOD. These results suggest that natural sources (long-range transport) dominate anthropogenic pollution sources over India and adjoining regions, at least during the dry season. This finding is important to argue against the common belief that Asian countries are the main sources of pollution when long-range transport, which is a natural source, is the main cause. Lockdown has provided an opportunity to test this through a natural simulation by turning down the anthropogenic activities.